Ocupação urbana em áreas de preservação permanente : o caso do manguezal da área continental de Vitória-ES - Reis, Débora Marchini (2013)
This research aims to diagnose the environmental impacts caused by the growth of urban occupations over the mangrove in the continental area of Vitória. It is justified by the gradual degradation of mangroves in Vitória that has inestimable importance to